Computer Science &Amp; Information Technology ( CS &Amp; IT ) 2013
DOI: 10.5121/csit.2013.3811
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison Between the Original Forms of Biogeography-Based Optimization Algorithms

Abstract: Biogeography-based optimization (BBO) is a new population-based evolutionary algorithm and one of meta-heuristic algorithms. This technique is based on an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Curves of fitness functions of the original and modified PMB for some selected functions 05, Table 3 shows the CPU time comparison between the modified PMB BBO. It can be clearly seen from Table 3 the CPU time, which means that (SPMB-BBO) by around 24.76% [20]. Table 3.…”
Section: Migration and Mutation Stagesmentioning
confidence: 85%
See 3 more Smart Citations
“…Curves of fitness functions of the original and modified PMB for some selected functions 05, Table 3 shows the CPU time comparison between the modified PMB BBO. It can be clearly seen from Table 3 the CPU time, which means that (SPMB-BBO) by around 24.76% [20]. Table 3.…”
Section: Migration and Mutation Stagesmentioning
confidence: 85%
“…Curves of fitness functions of the original and modified PMB for some selected functions 05, (b) f30-11, (c) f60-02, (d) f60-03 Table 3 shows the CPU time comparison between the modified PMB-BBO and the original PMB from Table 3 that the modified version can save around 32. that it is faster than even the simplified partial migration model % [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simplified Partial Migration Based BBO "SPMB-BBO" 4. Simplified Single Migration Based BBO "SSMB-BBO" From preceding study [20], it is shown that SMB-BBO and SSMB-BBO give poor performance but with lowest CPU time, while the performance comparison between PMB-BBO and SPMB-BBO shows that PMB-BBO gives better performance as the complexity, side constrains and/or dimensions of a given problem increases and as the number of islands decreases; and vice versa for SPMB-BBO. This judgment could be clearly observed if the mutation algorithm is not activated, because it compensates for the weakness of the migration algorithm.…”
Section: Biogeography-based Optimization (Bbo)mentioning
confidence: 99%